Factors affecting environmental performance in The Ectourism Industry in Bali Indonesia - I Made Darsana; Francisca Titing Koerniawaty (Institute of Computer Science (IOCS), 2023)
Environmental changes and global warming are also being felt in the tourism industry. The success of the tourism industry is highly dependent on the demand for tourism. International tourism is recognized as very vulnerable to crises or disasters. The main issues in this research are whether Green HRM is a predictor of environmental performance and whether the citizenship behavior of environmental organizations of employees acts as a mediator in the ecotourism industry in Bali, Indonesia. The purpose of this research is to find out the factors that affect environmental performance in the ecotourism industry in Bali, Indonesia. This type of research uses a quantitative approach with a cross sectional and non-experimental approach. The research design is also descriptive and explanatory in nature because it does not only focus on the current condition of green HRM but also explains the relationship between variables, namely Organizational Citizenship Behavior (Z) GHRM (X). The results of the study show that Green HRM is able to increase the OCB of employees in the Ecotourism Industry in Bali Indonesia. Green HRM has a positive and insignificant effect on Environmental Performance and Employee OCB has a positive and significant effect on Environmental Performance. Employee OCB is able to mediate the effect of Green HRM positively and significantly on environmental performance and the formation of environmental performance is more dominantly influenced by employee OCB.